Elite Domination and Lower Class Resistance in Ernest Cline’s Ready Player One - Dika Shafira Hidayat; Achmad Munjid (Lexicon, 2020)
This research examines Ernest Cline’s Ready Player One (2011), a popular science fiction novel. The objective of this research is to find out how a massive company called IOI (Innovative Online Industries) runs its domination against people in the novel. Furthermore, this paper also studies how the people resist the company’s domination. This study uses Marxist Theory since it investigates class, class conflict and struggle, domination, and resistance. The elements of the theory are identified in the novel and therefore analyzed to reach the objectives. The results of the analysis show that conflict is the reason of class grouping. In Ready Player One, the capitalist wants to expand its domination by winning the easter egg hunt while the proletariat resists it. It is concluded that class struggle and conflicts brings the proletariat to work together to resist the capitalist’s domination.